2020
DOI: 10.1002/gps.5410
|View full text |Cite
|
Sign up to set email alerts
|

Are serum cholesterol levels associated with cognitive impairment and depression in elderly individuals without dementia?: A retrospective cohort study in South Korea

Abstract: Objectives: As aging progresses, older adults experience several health changes, including changes in cholesterol levels, which increases their risk for other diseases. Older adults are particularly vulnerable to cognitive impairment and depression, which may be due to several factors. The aim of this study was to evaluate the association between serum cholesterol level and cognitive impairment and depression in older adults. Methods: This study used senior cohort data from the National Health Insurance Servic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 35 publications
0
2
1
Order By: Relevance
“…FBG represents the abnormality of glucose level and is recognized as a well-known risk factor for dementia [33,34], while we do not identify the causal association. In the association of TG, HDL-C, and dementia, the results also remain inclusive [35][36][37]. Our MR analysis does not find a causal relationship.…”
Section: Discussioncontrasting
confidence: 41%
“…FBG represents the abnormality of glucose level and is recognized as a well-known risk factor for dementia [33,34], while we do not identify the causal association. In the association of TG, HDL-C, and dementia, the results also remain inclusive [35][36][37]. Our MR analysis does not find a causal relationship.…”
Section: Discussioncontrasting
confidence: 41%
“…It is also an independent risk factor for coronary heart disease and ischaemic stroke,7 which increase the risk of cognitive impairment in older adults 8. However, conflicting results have been found regarding the correlation of cognitive impairment with serum total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C) and triglycerides levels 9 10. A case–control study showed that cognitive performance test results changed with levels of serum TC and LDL-C concentrations in older adults 11.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, a correlation between increased levels of TC, LDL-C, HDL-C and a lower risk of cognitive impairment was only observed in the population over 80 years old, but not in the 65–79 age group ( Lv et al, 2016 ). Moreover, there were studies suggested that TG is irrelevant to cognitive impairment ( Liu et al, 2020 , Han and Kim, 2021 , Yoshitake et al, 1995 , Forti et al, 2010 , Muller et al, 2007 ). The inconsistencies in these results can be attributed to factors such as sample size, demographic characteristics of the sample including age, gender, and ethnicity, time of blood testing, and length of follow-up.…”
Section: Humanmentioning
confidence: 99%